APLIKASI SISTEM PERSEDIAAN BARANG GUDANG PT. BERKAH PENA ILMU MENGGUNAKAN ANDROID STUDIO DAN METODE RAPID APPLICATION DEVELOPMENT (RAD) - Iman Alfajri; NM Faizah; Ryan Rakryan WP (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The purpose of the research is to make it easier for staff to record and report warehouse inventory, online or offline stores with this application where the application is designed so that it can be held in the hand and running, so the admin can monitor if there is stock taking in the warehouse. This inventory data application makes it very easy for staff in terms of appearance, use, and available features so that there is no need for employees to carry inventory paper when stock taking, no need to manually copy data during monthly inventory reports, and easy to see remaining inventory if anyone asks. UML (Unified Modeling Language) is used as an approach for modeling and in the application development process using the Rapid Application Development (RAD) method. The results show that a low level of accuracy in recording inventory can be overcome by using an Android-based barcode that replaces manual recording, providing a solution in the form of convenience in recording warehouse inventory data, online or offline stores, inventory applications with barcodes can be applied to applications based Android makes it easy for admins and users so that the process of recording the availability of goods will be faster and more accurate and this application can run well on various smartphones with the Android operating system.